L`arbitrage de haut niveau, une affaire d`équipe - Boyer, S.; Rix-Lièvre, G.; Récopé, M. (Movement & Sport Sciences - Science & Motricité, 2015)
Refereeing is often brought down to a process of individual decision-making. However, studying the characteristics of how decisions are made during a match entails considering the involvement of the members of the team of officials. Thus, our research investigates the motives and modalities of co-ordination between the team`s members. Six professional football matches have been observed and eighteen auto-confrontation interviews conducted with the referees and their assistants. The analysis highlights types of co-ordination relating to how the playing situation is recognized to be acceptable and how the players are shown what is possible. The officials` co-ordination is based on the situated recognition of each one`s prerogatives.